2021
DOI: 10.3389/fbioe.2021.607709
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Study on an Injectable Glycol Chitosan/Dibenzaldehyde-Terminated Polyethylene Glycol Hydrogel in Repairing Articular Cartilage Defects

Abstract: The normal anatomical structure of articular cartilage determines its limited ability to regenerate and repair. Once damaged, it is difficult to repair it by itself. How to realize the regeneration and repair of articular cartilage has always been a big problem for clinicians and researchers. Here, we conducted a comprehensive analysis of the physical properties and cytocompatibility of hydrogels, and evaluated their feasibility as cell carriers for Adipose-derived mesenchymal stem cell (ADSC) transplantation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Among them, an injectable chitosan hydrogel, which self-heals by Schiff-base linkage, has also been studied [14] , [15] , [16] , [17] , [18] . The self-healing chitosan hydrogel (GC-DP) was prepared by mixing glycol chitosan solution and DF-PEG solution, where glycol chitosan solution and DF-PEG solution were obtained by dissolving glycol chitosan and DF-PEG in distilled and deionized water, respectively [17] , [19] , [20] , [21] , [22] , [23] . The GC-DP hydrogel has shown feasibility in cell encapsulation and injection processes [19] , a positive effect on the repair of the zebrafish embryo neural system [20] , and the feasibility for use as 3D cell culture platforms [21] , and it was also used as a carrier for adipose-derived mesenchymal stem cells, showing that this transplantation achieved significant cartilage regeneration and repaired the cartilage-defect area in vivo experiments [23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, an injectable chitosan hydrogel, which self-heals by Schiff-base linkage, has also been studied [14] , [15] , [16] , [17] , [18] . The self-healing chitosan hydrogel (GC-DP) was prepared by mixing glycol chitosan solution and DF-PEG solution, where glycol chitosan solution and DF-PEG solution were obtained by dissolving glycol chitosan and DF-PEG in distilled and deionized water, respectively [17] , [19] , [20] , [21] , [22] , [23] . The GC-DP hydrogel has shown feasibility in cell encapsulation and injection processes [19] , a positive effect on the repair of the zebrafish embryo neural system [20] , and the feasibility for use as 3D cell culture platforms [21] , and it was also used as a carrier for adipose-derived mesenchymal stem cells, showing that this transplantation achieved significant cartilage regeneration and repaired the cartilage-defect area in vivo experiments [23] .…”
Section: Introductionmentioning
confidence: 99%
“…The self-healing chitosan hydrogel (GC-DP) was prepared by mixing glycol chitosan solution and DF-PEG solution, where glycol chitosan solution and DF-PEG solution were obtained by dissolving glycol chitosan and DF-PEG in distilled and deionized water, respectively [17] , [19] , [20] , [21] , [22] , [23] . The GC-DP hydrogel has shown feasibility in cell encapsulation and injection processes [19] , a positive effect on the repair of the zebrafish embryo neural system [20] , and the feasibility for use as 3D cell culture platforms [21] , and it was also used as a carrier for adipose-derived mesenchymal stem cells, showing that this transplantation achieved significant cartilage regeneration and repaired the cartilage-defect area in vivo experiments [23] . Furthermore, a chitosan-fibrin-based self-healing hydrogel was fabricated, and it successfully repaired the blood circulation of the ischemic hindlimbs of mice, indicating the feasibility of applying hydrogels to vascular repair [24] .…”
Section: Introductionmentioning
confidence: 99%
“…The combination of natural and synthetic polymers can play to their respective strengths and compensate for their weaknesses ( Peng et al, 2019 ; Li et al, 2021c ). Yang et al (2021) mixed injectable hydrogels of 2%DF-PEG/1.5%GCS, which significantly improved the mechanical properties and biocompatibility of hydrogels, and the hydrogels loaded with ADSCs promoted cartilage repair. Shi’s team researched and prepared an injectable hydrogel with natural antioxidant capacity.…”
Section: Materials Of Injectable Hydrogelsmentioning
confidence: 98%
“…Similar to TMJ condylar cartilage, the main materials used for knee cartilage regeneration are PEG, PGA, PLGA, PLA, PCL, and PVA. [81][82][83][84][85][86] The extensive researches on synthetic polymers benefit from their superior conditions. In contrast, the degradation rate of synthetic polymers is controllable and can be customized according to exact demands.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…An effective articular cartilage repair was found after placing these hydrogel scaffolds in Sprague-Dawley rats' knees for 8 weeks. [81] What's more, after a 5-year follow-up of patients implanted with PGA-HA implants, it was clear that the cartilage defect of the knee joint had been improved. However, a statistical analysis indicated that patients with tibial defects had less pain than those with femoral defects.…”
Section: Synthetic Polymersmentioning
confidence: 99%